Namudzaj Istiyáb al-Qiymah al-Ijtimaíyah bi Tathbiq Tadris al-Qiraáh li al-Mujtama’ fi Majlis Ta’lim al-Hidayah Langsa-Aceh/A Social Value Comprehension Model By Applying Teaching Reading to The Majlis Taklim Al-Hidayah Langsa - Aceh - Hatta Sabri; Nasruddin Nasruddin (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2023)
The many developments of taklim and remembrance majlis in the city of Langsa, emerged simultaneously with the development and application of Islamic sharia in Sukarejo Village, Langsa City, Aceh. Among the forms of recitation at the taklim assembly is studying Islamic sciences by reading Arabic-language books, such as issues of fiqh, monotheism and tasawwuf. This paper aims to describe the phenomenon of learning to read for the community at the Majlis Taklim Alhidayah, Sukarejo Village, Langsa, which is devoted to instilling social values. The phenomenon of religious studies at the al-Hidayah assembly is different from other study centers in the city of Langsa, which focus on reading Arabic-language book materials not only on aspects of fiqh, monotheism and tasawwuf morals. This research is a descriptive qualitative study, namely research with data collection methods by in-depth interviews, observation and documentation, then data analysis and discussion. And the results of this study, that the application of learning to read Arabic texts for the community at the al-Hidayah study assembly, Sukarejo village, Langsa Aceh city, is oriented towards inculcating social and religious values and includes material on tasamuh, family or mutual help, hospitality, protecting the environment. Then related to the role of parents in fostering children and the community, the values of mutual help and social activities. And this learning process can be used as a model for developing social values-based recitation.المستخلص: انتشرت نمت وطورت مجاليس التعليم للمجتمع بمدينة لانقسا مع تطبيق الشريعة الإسلام بآتشيه. من أنشطة التعليمية في المجاليس هي تدريس العلوم الإسلامية بطريقة قراءة الكتب العربية مثل في مسائل الفقهية والتوحيد ثم التصوف. يهدف هذا البحث لكشف ظواهر تدريس القراءة للمجتمع فى مجليس التعليم الهداية بقرية سوكارجوا لانقسا، التى تخص فيها تعليم القراءة في ضوء استيعاب القيمة الإجتماعية. فظواهر هذه العملية الجذابة وتفارق مجاليس أخرى بهذه المدينة، التى تراعي تعليم القراءة بالمواد المتعلقة بالنظرية الفقهية والأخلاف والتوحيد فقط. استخدم هذا البحث بالمنهج الكيفي الوصفي، وهو منهج جمع البيانات بطريقة المقابلة العميقة والملاحظة والتوثيقية، ثم تحليل البيانات ومناقشتها. وتوصل إلى نتيجة البحث فهي:  أن تطبيق تعليم قراءة النصوص العربية للمجتمع في مجليس التعليم الهداية قرية سوكارجوا بمدينة لانقسا أتشيه، توجه نحو غرس القيمة الاجتماعية والدينية. ويتضمن مادة عن التسامح، الأسرة أو المساعدة المتبادلة، الضيافة، حماية البيئة. ثم تتعلق بدور الوالدين في رعاية الأبناء والمجتمع، والقيم التعاون والأنشطة الاجتماعية. ويمكن استخدام هذه العملية التعلمية كنموذج لتطوير عملية التعليم للمجتمع في المجالس التعليمية.